Precipitation behavior, density, viscosity, and CO2 absorption capacity of highly concentrated ternary AMP-PZ-MEA solvents. (October 2022) - Apaiyakul, Rattanaporn; Nimmanterdwong, Prathana; Kanchanakungvalkul, Thitiya; Puapan, Papitchaya; Gao, Hongxia; Liang, Zhiwu; Tontiwachwuthikul, Paitoon; Sema, Teerawat
Highlights: Highly concentrated 6-7 M AMP-PZ-MEA solvents were successfully developed without precipitation. Proposed solvents contained high PZ:AMP molar ratios (1.25, 2.5, and 3.75) and minimum MEA concentrations (1.5 M and 2.5 M). The blends had same density range with 5 M MEA but much higher viscosity. In comparison with 5 M MEA, the proposed solvents had 56-71% higher CO2 absorption capacity. Abstract: This study explored potential of highly concentrated AMP-PZ-MEA solvent for capturing CO2 in terms of solvent precipitation, density, viscosity, and CO2 absorption capacity. It was found that most of the studied AMP-PZ-MEA solvents precipitated at high AMP and PZ concentrations and at high CO2 loading. The minimum possible MEA concentration (which can maintain a clear solvent) was 1.5 M for 6 M total amine concentration. It was also observed that an increase of AMP and/or PZ concentration in the 6 M blends induced the solvent precipitation. MEA was the only amine component that can be added to the blends to elevate the total amine concentration from 6 M to 7 M. As a result, the six AMP-PZ-MEA blends were suggested: 2:2.5:1.5, 1.3:3.2:1.5, 0.95:3.55:1.5 (for 6 M) and 2:2.5:2.5, 1.3:3.2:2.5, and 0.95:3.55:2.5 (for 7 M). The proposed blends are corresponding to PZ:AMP molar ratio of 1.25, 2.5, and 3.75, which are much higher than that of the first-generation AMP-PZ-MEA solvents. Regarding the visualized observation, there was no solid sediments observed throughout precipitation and CO2 absorption studies of the six blends. Interestingly, densities of the proposed blends were close to that of 5 M MEA, while their viscosities were much higher than that of 5 M MEA but were close to that of MDEA-PZ and AMP-PZ. Additionally, CO2 absorption capacities of the proposed 6 M and 7 M blends were 56-58% and 64-71% higher than that of 5 M MEA. These numbers are much higher than those of the first-generation AMP-PZ-MEA solvents. Graphical abstract: Image, graphical abstract